Role of HR Planning in Developing Employees to Improve Company Performance - Riandika Aji Mehendra; Ali Imron; Asro Bin Harun; Dika Hilaldi (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2026)
This study aims to analyze the role of human resource planning in developing employees to improve company performance, particularly by explaining how workforce forecasting, competency mapping, employee development, career management, and performance alignment contribute to organizational effectiveness. This study employed a qualitative descriptive method using a literature-based approach. Data were collected from secondary sources, including peer-reviewed journal articles, academic references, and relevant scholarly documents related to human resource planning, employee development, strategic human resource management, and company performance. The data were analyzed through qualitative content analysis by identifying, classifying, comparing, and interpreting major themes found in the literature. The results show that human resource planning functions as a strategic foundation for employee development by helping organizations determine workforce quantity, quality, competency needs, and future employee requirements. Effective HR planning supports employee development through training, career development, competency-based placement, succession planning, and continuous performance evaluation. The findings also indicate that ineffective HR planning may negatively affect company performance by creating structural ambiguity, inefficient resource utilization, increased costs, reduced employee welfare, and lower productivity. Conversely, systematic HR planning strengthens organizational readiness, improves employee capability, enhances work motivation, supports innovation, and contributes to sustainable company performance. Concludes that human resource planning should not be treated merely as an administrative function, but as a strategic instrument for building competent, adaptive, and performance-oriented employees who can support long-term organizational competitiveness.